HUBUNGAN INTENSITAS KEBISINGAN DI LINGKUNGAN KERJA DENGAN PENINGKATAN TEKANAN DARAH PADA PEKERJA PT X SEMARANG - Aqila Tischana Dewi; Tri Joko; Yusniar Hanani Darundiati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Noise from working environment can generate health impact on workers. Noise exposure which exceeds the treshold limit can affect the cardiovascular system, one of which is the increase of blood pressure. This research aims to determine the association between noise intensity and the increase of blood pressure on workers at PT X Semarang, a steel conduit manufacturing company. This is an observasional analitic study with cross-sectional design. The respondent amounted to 32 people taken with total sampling technique. The noise intensity measurement showed that the lowest noise intensity is in office area (59,7 dBA) while the highest is in factory B (88,12 dBA). The average age of the respondents is 40 years old with 8 years of working period. The average blood pressure before working is 124,06/81,34 mmHg and after working is 126,97/82,84 mmHg in which 71,9% respondents have an increase in systolic blood pressure and 68,8% in diastolic blood pressure. Bivariate analysis using fisher’s exact test showed that there is an association between noise intensity and the increase of diastolic blood pressure (p = 0,013; RP = 9,500; CI 95% = 1,641-54,994) but no association between noise intensity and the increase of systolic blood pressure (p = 0,075; RP = 5,938; CI 95% = 1,084-32,513). Among the confounding variables, there was an association between smoking habit and the increase of diastolic blood pressure (p = 0,022; RP = 7,000; CI 95% = 1,185-41,359) but not with the increase of systolic blood pressure (p = 0,433; RP = 2,600; CI 95% = 0,518-13,041). The conclusion of this research is noise intensity and smoking habit can affect the increase of diastolic blood pressure. The workers are advised to wear earplugs when working.